Optimization study of 2-hydroxyquinoxaline (2-HQ) biodegradation by Ochrobactrum sp. HQ1 - Subba Reddy, G. V. (3 Biotech, 2016)
A novel aerobic gram-negative bacterial strain capable of utilizing 2-hydroxyquinoxaline (2-HQ) as sole source of carbon and energy was isolated from Indian agricultural soil and named as HQ1. Strain HQ1 was identified as Ochrobactrum sp. on the basis of morphology, physico-biochemical characteristics and 16S rRNA sequence analysis. The generation time of Ochrobactrum sp. HQ1 on 2-HQ at log phase is 0.71 h or 42.6 min. The degradation of 2-HQ by HQ1 under various physico-chemical parameters was analysed by HPLC and observed to be optimum with a high inoculum density (1.0 OD) at pH 7–8, temperatures 37–40°C and a high concentration of 2-HQ (500 ppm). Degradation of 2-HQ was also improved when additional nitrogen sources were used and this was attributed to the enhanced growth of the bacterium on the readily available nitrogen sources. Analysis of 2-HQ degradation by GC–MS resulted in elucidation of the degradation pathway for HQ1, a novel observation for aerobic Gram-negative bacteria. These findings are a possible indication of the application of HQ1 in the bioremediation of pesticide/metabolite contamination. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13205-015-0358-6) contains supplementary material, which is available to authorized users.